PECULIARITIES OF PSYCHOPHYSIOLOGICAL ADAPTATION OF STUDENTS TO CONDITIONS OF ENFORCED SELF-ISOLATION DURING DISTANCE LEARNING - Sergeeva, Y.S.; Lebedeva, T.R.; Lubyshev, E.A.; Kubenin, S.S. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to determine the influence of the academic day in terms of distance learning during self-isolation on the psychophysiological state of students attributed to the preparatory health group. Methods and structure of the study. Sampled for the study were the 1st-year students (17-19 years old) studying at the Faculty of Humanities and Social Sciences at People's Friendship University of Russia, majoring in "Philosophy" and "Sociology". The students were split into 2 groups: Group I - boys (37 subjects) and Group II - girls (46 subjects). The study was conducted at the beginning of the academic year in the autumn and spring periods, that is, under the stressful impact the enforced self-isolation. Results and conclusion. The study enabled to identify a "critical period" in mastering the university curriculum: the initial period of adaptation, as a response to new learning conditions for students and the proposed curricular and extracurricular workload in a non-standard format.